2019
DOI: 10.1002/aic.16555
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of transition process from nucleate boiling to microbubble emission boiling under transient heating modes

Abstract: This study investigated the transition from nucleate boiling to microbubble emission boiling (MEB) on a small heating surface under transient heating modes. During the short unstable boiling process after critical heat flux with a rapid increase in wall temperature, capillary waves were observed over the vapor film at subcooling of 30–40 K. The visualization results in this process demonstrated that the partial collapse of vapor film induced strong jet toward the heating surface and therefore avoided complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 47 publications
4
15
0
Order By: Relevance
“…One can distinguish the growths of the bubbles much smaller than the heated surface. In the S‐MEB as shown in the rows (2) and (4), the vapor bubbles almost cover the heated surface, and exhibit violent oscillations by the growths and condensations as depicted by previous researches 8,9,18 . Such behaviors of the vapor bubbles were described as “some bubbles crash shrinking rapidly toward their center, and others collapse after being contracted in their middle” and “violent spouting of minute bubbles from the surface.” 17 The behaviors are almost identical despite the difference of Δ T sub .…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…One can distinguish the growths of the bubbles much smaller than the heated surface. In the S‐MEB as shown in the rows (2) and (4), the vapor bubbles almost cover the heated surface, and exhibit violent oscillations by the growths and condensations as depicted by previous researches 8,9,18 . Such behaviors of the vapor bubbles were described as “some bubbles crash shrinking rapidly toward their center, and others collapse after being contracted in their middle” and “violent spouting of minute bubbles from the surface.” 17 The behaviors are almost identical despite the difference of Δ T sub .…”
Section: Resultsmentioning
confidence: 72%
“…It has been indicated that stable MEB is realized under relatively high degree of subcooling Δ T sub ≔ T sat − T ∞ , where T sat is the saturation temperature under the pressure concerned, and T ∞ is the ambient temperature of the bulk. Effect of Δ T sub on the heat transfer characteristics were examined intensively 5‐9 . Not only the effect of the temperature of the bulk liquid, but also the characteristics of the heated surfaces and the geometries has been discussed; such as their wettability 10,11 and shape and/or size (on squared surface 10 ; in micro/mini channels 12,13 ; on wires 12,14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This temperature range is lower than the temperature where vapor explosion occurs, which is not the temperature of spontaneous nucleation; thus, non-steady heat conduction due to direct contact supports heat transfer. Figure 10 presents the surface temperature at CHF and onset of MEB as a function of subcooling, similar to Tang et al (2019b). In this study, both CHF and MEB onset data points in an open space at a subcooling of 40 K in Fig.…”
Section: Possibility Of Solid-liquid Direct Contact Based On Leidenfrmentioning
confidence: 58%
“…Shafaee et al [10] studied the heat transfer characteristics of corrugated tubes with R-600a at a high evaporating temperature (331 K); they found that the heat transfer coefficient at quality of 0.7 is 1.6 times that at a quality of 0.6, but the heat transfer coefficient at quality of 0.6 is only 1.2 times that at quality of 0.1. Tang et al [11] experimentally investigated nuclear boiling heat transfer characteristics in novel inter-micro-finned tube with water;…”
Section: Introductionmentioning
confidence: 99%